Kecerdasan Ekologis Dalam Meningkatkan Ketahanan Pangan Berkelanjutan: Kasus Petani Sagu di Distrik Makbon Kabupaten Sorong (Ecological Intelligence in Improving Sustainable Food Security: The Case of Sago Farmers in Makbon District, Sorong Regency) - Muzna Ardin Abdul Gafur; Niny Jeni Maipauw; Amir Amir (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
Sago is one of the staple foods of the people of Southwest Papua and is an important commodity supporting food security. Sago plants are spread across several villages in Makbon District. Along with increasing economic needs, there is a concern that the local wisdom of sago farmers will be eroded in their perspectives, attitudes, and actions towards the sago ecosystem. This study aims to describe ecological intelligence in the values ​​of local wisdom of sago farmers in Makbon District. Data was collected in three sago processing locations: Teluk Dore Village, Baingkete Village, and Malaumkarta Village. The scope of the study includes traditions, perspectives, attitudes, behaviors, and local knowledge of sago farmers in maintaining the ecosystem and utilizing sago forest resources. Data analysis was carried out descriptively and qualitatively. The results of the study showed several forms of local wisdom, including harvesting sago according to needs without excessive exploitation (egek tradition), maintaining and caring for sago groves wisely, and obeying ancestral messages not to burn grass around sago land to prevent sago forest fires (netal fugin oh). In addition, the involvement of all family members in the sago processing process provides experience for the next generation regarding sago processing techniques (ap solfagu). In general, the sago ecosystem in this area is maintained, and in Malaumkarta Village, sago cultivation efforts have been carried out by the community. The ecological intelligence of sago farmers in Makbon District is the main indicator in preserving the sago ecosystem to support sustainable food security.